Profitability Analysis among Actors of High-Quality Cassava Flour in South West Nigeria - BABATUNDE, Adeola Adefisayo; Yusuf, Sulaiman Adesina; Omonona, Bola Titus; Obi-Egbedi, Ogheneruemu (International Journal of Sustainable Agricultural Research, 2022)
High-Quality Cassava Flour (HQCF) as one of the value added products of cassava has the potential to revolutionizing the Nigeria cassava sector. Profitability of the actors in the production of HQCF in South-western Nigeria is therefore the subject of this study. A four multistage sampling technique was used to investigate the working efficiencies and practices of cassava farmers. Mapping surveys for all the areas of production and marketing of HQCF were produced. A total of 381 valid actors (311 cassava producers, 18 processors and 26 marketers) were used. The resulting data was were analysed using descriptive statistics and profitability analysis. Age, household size, and farming experience of the HQCF actors were; 48.3±8.46, 47.6±8.08, 44.1±6.79 years, 6.91±2.15, 5.26±1.03, 7.08±2.47 members, and 21.7±10.81, 8.4±2.11, 10±1.38 years, respectively. Profitability indicators were gross margin and net farm income. The HQCF actors were; ₦849,361.17 and ₦828,499.28/ha/year for cassava farmers. ₦46,028,307.98 and ₦43,761,365.97 for HQCF processors. Marketing margin was ₦8,249.88/year for HQCF marketers. Profitability Index (PI) for the actors were 0.98 and 0.35 cassava farmers and HQCF processors respectively.